Confining SnSe nanobelts in 3D rGO aerogel for achieving stable and fast lithium storage. (July 2019) - He, Cui; Wang, Cheng; Li, Feng; Wang, Xiaojun; Zhou, Yiming; Wu, Ping
Graphical abstract: Highlights: In situ selenization from Sn nanorods to SnSe nanobelts within aerogel framework. Uniformly confining SnSe nanobelts within reduced graphene oxide aerogel. Enhanced Li-storage performances in terms of capacity, cycle, and rate capabilities. Abstract: Tin selenide (SnSe) shows great potential as a promising anodic candidate of commercial graphite in Li-ion batteries (LIBs), but its practical application is hampered by huge volume change-induced poor cycle span. Herein, a gel-enabled selenization route has been developed for uniformly confining SnSe nanobelts within reduced graphene oxide aerogel (SnSe NB@rGO framework). These unique structural and compositional features make the SnSe NB@rGO framework electrode to show high revisable capacities (620 mA h g −1 after 200 cycles at 0.1 A g −1 ), high rate capability (626 and 551 mA h g −1 at 0.5 and 1 A g −1, respectively) and ultralong cycle span (412 mA h g −1 after 800 cycles at 1 A g −1 ).